Variedades de milho para a produção de minimilho e qualidade pós-colheita em sistema orgânico de cultivo - Lopes, Adelmary Prestes (2012)
Baby corn is the name given to the yet immature corn ear, that is, non-pollinated, 2 or 3 days after the corn stigma-style emission. Different kinds of corn varieties, as sweet corn, popcorn and even common corn, have been evaluated to the baby corn production. Thus, this study had the aim of evaluating five kinds of corn for baby corn production and the post-harvest quality in organic system cultivation. The research was developed in a private area, under organic management, in the town of Cascavel (Paraná) in 2011, from of October to November. It was conducted in a completely randomized experimental design with four replications for the production components evaluation and for the product post-harvest on 5 x 2 x 4 factorial arrangement for the five varieties (IPR 114, PC 0402, PC 0404, BR 106 and BRS Ângela) and by two ways of stowage (with and without straw) and storage time (0, 4, 8 and 12 days). The data was submitted to ANOVA, and the averages were compared by the Scott-Knott test at 5% of probability and by regression analysis with the statistical software SISVAR (5.3 version). The experimental area was divided in portions of 4.0 meters of length x 4.2 meters of composed width with which one of the four plant rows far-between about 4.0 meters with four replications. For data obtainment, the two useful central plant rows were chosen. The agronomical characteristics were evaluated: number of ears by plant (EP), plant height (AP), first plant insertion height (EI), length of ear without straw (CESP) and with straw (CECP), diameter of ears with straw (DECP) and without straw (DESP), mass of ears with straw (MECP) and without straw (MESP), productivity of baby corn with straw (PTMCP) and without straw (PTMSP), commercial production of baby corn without straw (PCMSP), and commercial corn yield (RMC). For the product post-harvest, these aspects were analyzed: loss of mass (PM) and color (L*, a*, b*, C* and H*) in storage time of 0, 4, 8 and 12 days. The obtained results indicate that the evaluated varieties were classified within commercial standards, since PC 0404 and BRS Ângela are the most indicated for baby corn obtainment. The loss of mass in the stowage with and without straw was lower for the varieties PC 0402 and BR 106. For the color parameter (L*) in the treatment with straw, the varieties PC 0402 and BR 106 presented high luminosity, and in the treatment without straw the varieties IPR 114 and PC 0402 were better. On the intensity of red/green coloring (a*) in the stowage without straw, the varieties BR 106 and IPR 114 presented lower degradation of color; with straw, IPR 114 and PC0402 did the same. For the coordinate (b*) in the treatment of the ears with straw, the varieties PC 0402 and PC 0404 presented the highest numbers; in the treatment of ears without straw, IPR 114 e PC 0402 did he same. On the hue angle (H*), the varieties PC 0402 and PC 0404 presented the highest coloring angle for the two stowage ways. For the chroma index (C*) in the stowage with straw, the variety PC 0402 obtained more intense coloration; in the stowage without straw, PC 0402 and IPR 114 did it.